The Production of Food Commodities in Indonesia: Climate Change and Other Determinants - Ivan Hannoeriadi A.; Hermanto Siregar; Alla Asmara (Jurnal Agrisep)
Climate change has become a global issue since it has a wide range of effects on a country's socioeconomic situations, including food security. The El Nino Southern Oscillation (ENSO) is a climatic change phenomenon in Indonesia that has three phases: El Nino, Normal, and La Nina. This phenomenon has an impact on rainfall intensity, which bring another impact on the agricultural sector, particularly the sub-sector of food crops. This study uses static panel data methods to examine the impact of climate change and other determinants on food production such as rice, corn, and soybeans. The cross-sectional data are concentrated on the provinces of Java that have become the production centers of rice, corn and soybeans, and the other four provinces with the highest yields of the above three products, and the time data series used from 2009 to 2017.The results obtained show that El Nino has a significant effect on decreasing rice and corn production and increasing soybean production. While La Nina has a significant effect on increasing the production of the three commodities studied. Fertilizer subsidy has a significant effect on increasing the production of the three commodities studied meanwhile productivity significantly impact rice and corn productions.